A pseudo-two-dimensional model of an n-channel MOSFET under the influence of ionizing radiation - Chauhan R.K.; Dasgupta S.; Chakrabarti P. (My University, 2025)
A pseudo-two-dimensional model has been developed for determining the radiation-induced changes in the characteristics of an n-channel metal-oxide-semiconductor-field-effect transistor (MOSFET) during exposure to ionizing radiation as well as in the post-irradiated condition. The ionizing radiation-induced excess carriers in the semiconductor as well as changes in the interface states and build-up of oxide-trapped charges at Si-SiO2 interface have been incorporated in the basic model equations for analysing the device under exposure to ionizing radiation. A model has been proposed that can examine the behaviour of the device during exposure to ionizing radiation. This model enables one to determine the ID-VD and transfer characteristics of the device by considering the field-dependent mobility of the surface channel in the unirradiated condition, during exposure to ionizing radiation as well as in post-irradiated condition. The results obtained on the basis of the model in the irradiated as well as post-irradiated condition have been compared and contrasted with available experimental and simulated results.